Reduction of oxidative stress does not affect recovery of myocardial function: warm continuous versus cold intermittent blood cardioplegia. Issue 5 (May 1997) - Biagioli, B.; Borrelli, E.; Maccherini, M.; Bellomo, G.; Lisi, G.; Giomarelli, P.; Sani, G.; Toscano, M.
Abstract : OBJECTIVE: To compare oxidative stress after cardiac surgery in patients treated with two different methods of myocardial protection: warm continuous versus cold intermittent blood cardioplegia. To correlate oxidative stress with postoperative myocardial dysfunction. DESIGN: Prospective, randomised, double blind, trial. SETTING: Institutional centre of cardiovascular surgery. PATIENTS: 20 patients were selected for coronary artery bypass surgery (CABG) on the following basis: stable angina, ejection fraction > 50%, double or triple vessel disease, no previous CABG or associated disease. Patients were randomised to two groups of 10 patients each. INTERVENTIONS: Patients underwent CABG with one of two different methods of myocardial protection and cardiopulmonary bypass. CBC group: intermittent cold blood antegrade-retrograde cardioplegia with moderate hypothermic cardiopulmonary bypass; WBC group: continuous warm blood antegrade-retrograde cardioplegia with mild hypothermic cardiopulmonary bypass. MAIN OUTCOME MEASURE: The index of oxidative stress used was the alteration of whole blood and plasma glutathione redox status. Samples were collected from the coronary sinus and peripheral vein before anaesthesia (T1), before aortic unclamping (T2), 15 minutes (T3), and 30 minutes (T4) after unclamping. Haemodynamic parameters were measured with thermodilution techniques. RESULTS: Oxidised glutathione and glutathione-cysteine mixed disulphide significantly increased in the coronary sinus plasma in the CBC group, and the overall redox balance of glutathione was decreased (P < 0.01) at T2-T4 versus T1, and compared with the WBC group. Comparable results were obtained for coronary sinus blood. There was no correlation between postoperative haemodynamic measurements and oxidative stress markers. CONCLUSIONS: Oxidative stress was significant in patients undergoing CABG using cold blood cardioplegia, while the warm technique minimised the effects of ischaemia. However, oxidative stress was not correlated with myocardial dysfunction following CABG.